2021
DOI: 10.3390/brainsci11040481
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography and High-Density Electroencephalography Study of Acoustic Event Related Potentials in Early Stage of Multiple Sclerosis: A Pilot Study on Cognitive Impairment and Fatigue

Abstract: Cognitive impairment (CI) is a common and disabling symptom of Multiple Sclerosis (MS) with a negative impact on daily living. In this pilot study, we applied magnetoencephalography (MEG) and high density (hd) electroencephalography (EEG) study to evaluate acoustic P300 features in a cohort of early MS. Sixteen MS patients (pwMS) and 19 healthy controls (HCs) matched for age and gender underwent an MEG-/(hd)-EEG-co-recording, using 306-channel Vectorview and 64 scalp electrodes. CI was assessed using Rao’s Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…We found 38 studies that presented results for a concomitant occurrence of P300 and alpha power (or amplitude). In 17 studies using EEG, results indicated an overlap in cortical regions of P300 and alpha amplitude decrease, as well as a similar time windows of their occurrence (Peng et al, 2012, Chen et al, 2013, Dong et al, 2015, Shou et al, 2015, Tang et al, 2015, Wu et al, 2015, Fabi et al, 2017, López-Caneda et al, 2017, Vilà-Balló et al, 2017, Fabi et al, 2018, Michelini et al, 2018, Román-López et al, 2019, Kao et al, 2020, Yu et al, 2020, Zhang et al, 2020, Nikolin et al, 2021, Paolicelli et al, 2021). Similar observations were made using MEG (Ishii et al, 2009).…”
Section: Introductionmentioning
confidence: 86%
“…We found 38 studies that presented results for a concomitant occurrence of P300 and alpha power (or amplitude). In 17 studies using EEG, results indicated an overlap in cortical regions of P300 and alpha amplitude decrease, as well as a similar time windows of their occurrence (Peng et al, 2012, Chen et al, 2013, Dong et al, 2015, Shou et al, 2015, Tang et al, 2015, Wu et al, 2015, Fabi et al, 2017, López-Caneda et al, 2017, Vilà-Balló et al, 2017, Fabi et al, 2018, Michelini et al, 2018, Román-López et al, 2019, Kao et al, 2020, Yu et al, 2020, Zhang et al, 2020, Nikolin et al, 2021, Paolicelli et al, 2021). Similar observations were made using MEG (Ishii et al, 2009).…”
Section: Introductionmentioning
confidence: 86%
“…The included studies used a variety of study designs to detect, quantify and examine MS-related fatigue. The 19 articles, shown in Table 1, employed the following study designs: 5 studies case–control studies (Buyukturkoglu et al, 2017; Conte et al, 2016; Gscwind et al, 2016; Russo et al, 2017; Vecchio et al, 2017), 3 cross-sectional studies (Chaves et al, 2019; Newland et al, 2021; Paolicelli et al, 2021), one prospective-observational study (Chalah et al, 2019); one correlational (Russo et al, 2017); one single blind, within-subject design (Fiene et al, 2018), and one cross-over study (Muñoz-Paredes et al, 2022). Seven of the 19 studies utilized a double-blind RCT study design.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 5 EEG studies (Buyukturkoglu et al, 2017; Gschwind et al, 2016; Newland et al, 2021; Paolicelli et al, 2021; Vecchio et al, 2017). Three of these were case–control studies (Buyukturkoglu et al, 2017; Gschwind et al; Vecchio et al) which collected and analyzed EEG data in fatigued MS patients, including functional connectivity at rest (FCR) between hemispheric homologous areas, and performed correlational analysis which revealed a relationship between cognitive fatigue and EEG data.…”
Section: Eeg Studiesmentioning
confidence: 99%
“…VEP , MEP 14,20,21,25,31,32,[38][39][40][41][42][43][44][45] , AEP 8,16,17,28 , SSEP 10,17,20,21,28,35,36,43,[46][47][48] • Longer VEP latencies correlate with retinal fibres are below norm 7,15,18,23,27,37 • Combination of EPs can predict MS progression after 20 years 11 , falls within one year, EDSS longitudinally 20,21,25,28,3146 , brain stem dysfunction 17 • Combination of EPs show stronger correlation with baseline EDSS than MRI white lesion burden 28 Oddball paradigm 49,63 • The delayed P300 peak reveals the inverse correlation between its amplitude and the mental fatigue level 49 • ERPs during the visual oddball task are correlated with processing speed at baseline in PwMS 63 Resting state 52,…”
Section: Eeg and Epsmentioning
confidence: 99%